Non -fatal overdose among people who inject drugs in Tehran, Iran - Mehdi Noroozi; Peter Higgs; Azadeh Bayani; Bahram Armoon; Ali Nazeri Astaneh; Ladan Fattah Moghaddam; Mohammad Askari (Substance Abuse Treatment, Prevention, and Policy, 2020)
Abstract Background With increasing frequencies of non-fatal overdose in people who inject drugs (PWID), it is essential to improve our knowledge about associated risk factors for overdose to inform overdose prevention and assistance programs. The aim of present study was to determine the prevalence of non-fatal overdose and the associated risk factors among PWID in Tehran, Iran. Methods Snowball sampling was used to collect data from 465 participants in Tehran using a cross-sectional survey. Consenting participants who reported drug injecting in the past month and were able to speak and comprehend Farsi enough to respond to survey questions were interviewed. The endpoint of interest was non-fatal overdose in the previous 6 months, or answering “Yes” to the question: “In the last six months, have you ever overdosed by accident? (at least once)”. We used STATA v. 14 for this analysis. Statistical significance was defined as p < 0.05 for all analyses. Results Of 465 PWIDs who participated in this study, all were male, and about half had less than a high school education. The prevalence of self-reported non-fatal overdose in the past 6 months was 38% (CI95%: 34, 43%). Our findings indicate that characteristics and behaviors that were associated with an increased risk of experiencing an overdose in the past 6 months were drug use initiation under 22 years (AOR =2.2, P < 0.05), using methamphetamine (AOR =2.8, P < 0.05), and using multiple drugs at the same time (AOR =2.1, P < 0.05). Also, more recent initiates to injecting (< 2 years) had an increased risk of experiencing an overdose in the past 6 months. The odds of experiencing a non-fatal overdose among PWIDs who regularly attended NSP were 0.6 times less than for those who did not attend regularly (OR = 0.6,95% CI: 0.2–0.9). Conclusion Methamphetamine and alcohol use were the most significant association for non-fatal overdose among PWIDs. Our results indicate that intervention and prevention initiatives seeking to reduce overdoses among PWIDs should not only be focused on the primary drug used but also the use of alcohol and poly-drug use.